Figurative Language in Songs in Student’s Book for Senior High School - Barli Bram; Anchieta Ave Avillanova (Soshum: Jurnal Sosial dan Humaniora, 2019)
Songs are increasingly used by teachers to teach English because students can learn many things from songs, such as vocabulary items and figurative language. However, sometimes the use of songs in the classroom only covers the surface of the discussion. Students need to be able to understand songs deeper by learning the figurative language. It is not easy to understand figurative language because people can interpret the meaning of it freely based on the context. Learning figurative language becomes important because it is found to give four beneficial aspects to students. Therefore, this study analyzed figurative language used in three songs in “Student’s Book 2 for Senior High School Students Grade XI”, which can be used by students to learn about songs deeper by understanding figurative language easily. This qualitative study can also be a consideration for the teachers and those who design the learning materials to include figurative language in the song’s part in the textbook.